Is Animal-Assisted Therapy for Minimally Conscious State Beneficial? A Case Study - Boitier, Jacqueline P.; Huber, Marion; Saleh, Christian; Kerry, Matthew J.; Hund-Georgiadis, Margret; Hediger, Karin (Frontiers in Psychiatry, 2020)
Objective: The goal of this single case study was to qualitatively investigate the effects of animal-assisted therapy in a patient in a minimally conscious state. Method: We present a 28-year-old female patient in a minimally conscious state following polytrauma after a sports accident leading to cerebral fat embolism causing multiple CNS ischemic lesions. She received eight animal-assisted therapy sessions and eight paralleled control therapy sessions over four weeks. We investigated the reactions of the patient during these sessions via qualitative behavior analysis. Results: The patient showed a broader variability and higher quality of behavior during animal-assisted therapy compared to control therapy sessions. Conclusion: The observed behavioral changes showed higher arousal and increased awareness in the presence of an animal. The presented case supports the assumption that animal-assisted therapy can be a beneficial treatment approach for patients in a minimally conscious state.